If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 + -7x = 5x + 148 Reorder the terms: 4 + -7x = 148 + 5x Solving 4 + -7x = 148 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 4 + -7x + -5x = 148 + 5x + -5x Combine like terms: -7x + -5x = -12x 4 + -12x = 148 + 5x + -5x Combine like terms: 5x + -5x = 0 4 + -12x = 148 + 0 4 + -12x = 148 Add '-4' to each side of the equation. 4 + -4 + -12x = 148 + -4 Combine like terms: 4 + -4 = 0 0 + -12x = 148 + -4 -12x = 148 + -4 Combine like terms: 148 + -4 = 144 -12x = 144 Divide each side by '-12'. x = -12 Simplifying x = -12
| (3+6g)12= | | 3x-9=7x-9 | | y=x^2+10x+16 | | 12+12y=10y-12 | | 4x-20+3x+15=100 | | 9-7x=-x-39 | | -5+3x=x-7 | | 9x+16=0 | | 2n(7n+8)=n+8 | | (x+a)(x+b)=(x+c)(x+d) | | 48-4x=5x+16 | | -28-10x=7x+23 | | 2x+10=-12-9x | | 4[3t+8]=3a+12 | | .2x-8=-2-1 | | [3x-7]-5=-3 | | x^4-12x^2-64=0 | | 5x-3=14x+5 | | 1.6q-4.5-4.5q=-3.9q-4.4 | | [5x+9]+6=1 | | 4x-20+3x+13=100 | | 4b-8=10-b | | x^4+8x^2+15=0 | | 4(h+1)=2(5h+6) | | 8x^5-25y^3+80x^4-x^2y^2+20x^3-10xy^3=0 | | 6x+27=13x-57 | | 6x+4x+4+9=7x+3+2x | | 8(x+1)=9+8x | | [a-3]-14=-6 | | 4x+4-1=-9x+7 | | 3ax-2=5bx+7 | | 10x+4+3+6=7x+3+6x |